HIGH FREQUENCY in vitro PLANTLET REGENERATION FROM LEAF, NODE AND SHOOT TIP EXPLANTS OF Corynandra felina (L.f.) Cochrane & Iltis, AN IMPORTANT ENDEMIC MEDICINAL PLANT IN PENINSULAR INDIA (Applied Biological Research, 2023)
An efficient in vitro plant regeneration protocol using leaf, node and  shoot tip has been developed in Corynandra felina (L. f.) Cochrane &  Iltis., an endemic medicinal herb in peninsular India. The above explants, taken from field-grown plants, were sterilized, and then  cultured on Murashige and Skoog's (MS) medium supplemented with  various concentrations of 6-benzylaminopurine (BAP, 0.5-3.0 mg L-1),  thidiazuron (TDZ, 0.25-1.25 mg L-1) and kinetin (Kn, 0.5-3.0 mg L-1)  either alone or in combination with indole-3-acetic acid (IAA, 0.25-1.0 mg L-1). Maximum number of shoots (48.3 ± 0.59) with average shoot  length of 1.4 ± 0.57 cm were regenerated directly from the leaf explants  grown on MS medium supplemented with TDZ (0.5 mg L-1) + IAA  (0.25 mg L-1). Maximum number of shoots (5.4 ± 0.38 and 6.2 ± 0.43)  with shoolength (1.9 ± 0.66 and 2.2 ± 0.19 cm) were observed in node  and shoot tip explants, respectively, when cultured on MS medium  supplemented with TDZ (0.5 mg L-1) + IAA (0.25 mg L-1). Tiny shoots  from leaf, node and shoot tip explants were elongated (5.6 ± 0.40) on  MS medium enriched with 1.0 mg L-1 GA3. The elongated shoots were  rooted (90%) on half-strength MS medium fortified with 1.0 mg L-1 IBA. The regenerated plantlets when transferred to the field showed  89% plant survival. For the first time, we report direct plantlet  regeneration in Corynandra felina using leaf explants.
Keywords: Corynandra felina; leaf; node; regeneration; shoot tip; thidiazuron